Kajian Kerusakan Struktur Gedung Fakultas Kesehatan Masyarakat UNAND Akibat Kebakaran Tanggal 8 Mei 2025 - Jeply Murdiaman Guci; Jafril Tanjung; Taufik Alhakim Iskandar (Jurnal Bangunan, Konstruksi & Desain, 2026)
The fire that occurred at the Faculty of Public Health (FKM) Building of Universitas Andalas on May 8, 2025 raised concerns regarding the serviceability and structural safety of the building before it could be reused as an educational facility. Post-fire building conditions may experience degradation of material quality and damage to both structural and non-structural elements; therefore, a comprehensive technical evaluation in accordance with applicable building regulations is required. This study aims to evaluate the condition and serviceability of the main structural components of the FKM building after the fire and to formulate technical repair recommendations to ensure the safety and security of building users. The research method was carried out through field observations and non-destructive testing of reinforced concrete structural elements, including visual inspection, measurement of structural element dimensions, evaluation of verticality, concrete hammer testing, and identification of cracks and deformations. In addition, inspections were conducted on non-structural elements and supporting building materials affected by the fire, such as roof structures, ceilings, partitions, and canopy elements, to identify the level of damage and the need for repair or replacement. The evaluation results indicate that the main structural elements, namely columns, beams, and floor slabs, still meet technical requirements and structural serviceability criteria, with concrete quality relatively consistent with the original design, namely K-250 or equivalent to a concrete compressive strength (fc’) of 20.75 MPa. No significant damage was found in the main structural elements that could compromise the building’s integrity. However, several non-structural elements and roof structures—particularly steel purlins, ceilings, partitions, and wooden components of the canopy roof (drop-off)—sustained damage due to heat and fire exposure and therefore require repair and replacement. The conclusion of this study states that the FKM Universitas Andalas building is generally still suitable for use, provided that comprehensive repairs are carried out on damaged components, strengthening of affected roof structural elements is implemented, and the fire protection system is improved. The technical recommendations produced are expected to serve as a reference in the building rehabilitation process so that the facility can be safely reused in accordance with building safety standards.